Respiratory Viral Infection Alters the Gut Microbiota by Inducing Inappetence - Helen T. Groves (American Society for Microbiology, 2020)
ABSTRACT Respiratory viral infections are extremely common, but their impacts on the composition and function of the gut microbiota are poorly understood. We previously observed a significant change in the gut microbiota after viral lung infection. Here, we show that weight loss during respiratory syncytial virus (RSV) or influenza virus infection was due to decreased food consumption, and that the fasting of mice altered gut microbiota composition independently of infection. While the acute phase tumor necrosis factor alpha (TNF-α) response drove early weight loss and inappetence during RSV infection, this was not sufficient to induce changes in the gut microbiota. However, the depletion of CD8+ cells increased food intake and prevented weight loss, resulting in a reversal of the gut microbiota changes normally observed during RSV infection. Viral infection also led to changes in the fecal gut metabolome, with a significant shift in lipid metabolism. Sphingolipids, polyunsaturated fatty acids (PUFAs), and the short-chain fatty acid (SCFA) valerate were all increased in abundance in the fecal metabolome following RSV infection. Whether this and the impact of infection-induced anorexia on the gut microbiota are part of a protective anti-inflammatory response during respiratory viral infections remains to be determined. IMPORTANCE The gut microbiota has an important role in health and disease: gut bacteria can generate metabolites that alter the function of immune cells systemically. Understanding the factors that can lead to changes in the gut microbiome may help to inform therapeutic interventions. This is the first study to systematically dissect the pathway of events from viral lung infection to changes in gut microbiota. We show that the cellular immune response to viral lung infection induces inappetence, which in turn alters the gut microbiome and metabolome. Strikingly, there was an increase in lipids that have been associated with the resolution of disease. This opens up new paths of investigation: first, what is the (presumably secreted) factor made by the T cells that can induce inappetence? Second, is inappetence an adaptation that accelerates recovery from infection, and if so, does the microbiome play a role in this?